Miskonsepsi Evaluasi Kelembagaan Pendidikan Islam Dalam Sistem Pendidikan Nasional di Indonesia - Damas Ahmad Yunus; Hermansyah Hermansyah; Lia Kurniati (Al-Khair Journal: Management Education, 2024)
Abstract: The evaluation of Islamic education institutions in the national education system in Indonesia often occurs misconceptions, marked by some people still consider that the concept of evaluation used by Islamic educational institutions is still wrong. The purpose of this study is to describe and analyze misconceptions of institutional evaluation of Islamic education in the national education system. Using descriptive qualitative methods. The results of the study can be concluded that the misconception of institutional evaluation of Islamic education in the national education system is an assessment technique for the behavior of students based on comprehensive calculation standards and all aspects of mental, psychological and spiritual life, religion. The Indonesian education system consists of several levels according to the level of development, ability and goals achieved by students. Starting from basic education (SD), (SMP), (SMA), and higher education. Misconceptions about the evaluation of Islamic educational institutions in the national education system are misconceptions about the purpose of evaluation because there are some people who consider that the main purpose of evaluation is to assess the success of individuals or schools in achieving academic achievement only, so it can be suggested that to improve the understanding of the concept of evaluation in Islamic educational institutions so that there are no misconceptions in the national education system in Indonesia.Keywords: Misconception, Evaluation, Islamic education institutions, national education system  Abstrak: Evaluasi kelembagaan pendidikan Islam dalam sistem pendidikan nasional di Indonesia sering terjadi miskonsepsi, ditandai dengan beberapa orang masih menganggap bahwa konsep evaluasi yang digunakan Lembaga pendidikan Islam masih keliru. Tujuan penelitian ini untuk mendeskripsikan dan menganalisis miskonsepsi evaluasi kelembagaan pendidikan Islam dalam system pendidikan nasional. Menggunakan metode kualitatif deskriptif. Hasil penelitian dapat disimpulkan bahwa miskonsepsi evaluasi kelembagaan pendidikan Islam dalam system pendidikan nasional merupakan teknik penilaian terhadap tingkah laku anak didik berdasarkan standar perhitungan yang bersifat komprehensip dan seluruh aspek-asepk kehidupan mental psikologi dan spiritual religius. Sistem pendidikan Indonesia terdiri atas beberapa tingkatan sesuai dengan level perkembangan, kemampuan dan tujuan yang di raih peserta didik. Mulai dari pendidikan dasar (SD), (SMP), (SMA), dan Pendidikan tinggi. Miskonsepsi tentang evaluasi Lembaga pendidikan Islam dalam sistem pendidikan nasional yaitu miskonsepsi tentang tujuan evaluasi disebabkan terdapat beberapa orang yang menganggap bahwa tujuan utama dari evaluasi adalah untuk menilai keberhasilan individu atau sekolah dalam mencapai prestasi akademik saja, sehingga dapat disarankan bahwa untuk meningkatkan pemahaman konsep evaluasi dalam kelembagaan pendidikan Islam agar tidak terjadi miskonsepsi dalam system pendidikan nasional di Indonesia.Kata Kunci: Miskonsepsi, Evaluasi, Kelembagaan pendidikan Islam, system pendidikan nasional